PTU-173 Feasibility study of safety and cost effectiveness of using johan forceps as endoloop pushers for laparoscopic appendicectomy. (22nd June 2015) - Siddique, K; Khan, K; Offori, T
Abstract : Introduction: Background : The base of appendix can be secured using endoloops or endoscopic stapler. The authors have reported the use of Johan forceps as endoloop pushers for laparoscopic appendicectomy. Method: Aims : To evaluate the safety and cost effectiveness of this technique. Patients and methods : A prospectively collected data of all patients who underwent laparoscopic appendicectomy by this technique between 2012 till 2014 was reviewed. Base of the appendix was secured using three standard extra-corporeal endoloops deployed with Johan's forceps utilising one vicryl tie. Demographics, operative findings, post-operative complications and readmissions were recorded and analysed. Results: Total number of patients was 120. There were 72 (60%) males while rest were female with an age of *24 (14–77). Grossly inflamed appendix (including perforation, localised abscess) was noted in 76% of cases. No peri-operative complications were reported. The post-op stay was *2 (1–5) days (* represents median). Complications include 7 (5.8%) wound infections which were managed conservatively. 9 patients were re-admitted due to reasons unrelated to the surgical technique. The cost of one vicryl tie was £0.5 Vs £49.80 (for 3 standard endoloops available in the market). The cost analysis showed johan assisted appendicectomy to be 99 times cheaper than the standard marketed endoloops. Conclusion: Our series involving various surgeons employing the standard technique of using the Johan forceps as endoloop knot pushers shows that it is a feasible and safe technique with promising results. The technique has been practised in various hospitals and provides a cheap and safe alternative to the standard endoloops available in the market. Disclosure of interest: None Declared.